Efeitos da eletroestimulação percutânea na incontinência urinária e qualidade de vida pós-prostatectomia: registro de seis casos - Sousa, Mabel Araujo de (2011)
Introduction: Radical prostatectomy surgery is the best treatment currently adopted by detecting prostate cancer. The urinary incontinence is one more common and difficult to treat postoperative complications, which causes a negative impact on quality of life of the individual prostatectomy . The surface electrical nerve stimulation involves the transmission of electrical impulses from an external stimulator for peripheral nerve through surface electrodes attached to skin. It is an easy and efficient technique, widely used for pain relief, rehabilitation and muscle strengthening. Objective: To analyze the effect of T10-L2 percutaneous electrical stimulation, in individuals with urinary incontinence who underwent radical prostatectomy by the laparoscopic technique. Methods: Six patients had previously undergone radical prostatectomy were submitted to 20 sections of surface electrical stimulation with frequency of 4 Hz, pulse width of 1ms during 20 minutes. All subjects fillid a quality of life - International Consultation on Incontinence Questionnaire- Short FormI - ICIQ-SF questionnaire evaluating. Results: Results showed reduction in the use of the number of pads, number of leaks before and after treatment, and reduced voiding frequency and consequent improvement in quality of life. No side effects were reported. Conclusion: Percutanous electrical stimulation in T10-L2 may be an effective technique to treat urinary incontinence (UI) after radical prostatectomy video laparoscopy